Sodium dodecyl sulphate-treated nanohydroxyapatite as an efficient shale stabilizer for water-based drilling fluids - Oseh, Jeffrey O.; Norddin, M. N. A. M.; Ismail, Issham; Duru, Ugochukwu I.; Ngouangna, Eugene N.; Gbadamosi, Afeez O.; Agi, Augustine Aja; Yahya, Muftahu N.; Abdillahi, Abdirahim O.; Oguamah, Ifeanyi A.; Omar, Shaziera B. (Elsevier B.V., 2024)
Drilling water-sensitive shale formations often leads to wellbore instability, resulting in drilling problems because of the clay's high-water affinity. To solve this problem, different nanoparticles (NPs), such as nanosilica, have been used to formulate water-based muds with potassium chloride (KCl-WBM). Nevertheless, the unmatched pore size of shale pores when using nanosilica fails to completely prevent shale swelling and dispersion. This study discusses the effects of KCl-WBM with sodium dodecyl sulphate-treated nanohydroxyapatite (nHAp/SDS) on shale swelling inhibition through various laboratory techniques. These techniques encompass the linear swell meter (LSM), the dynamic linear swell meter (DLSM), hot-rolling dispersion, suspension stability, and pore structure characterization of shale. The rheological and filtration characteristics of nHAp/SDS and compatibility tests were also studied, and the results were compared with those of nanosilica and KCl-WBM. At all concentrations, the performance of the nHAp/SDS test fluids surpassed that of nanosilica. When compared with KCl-WBM system at 10 cP and 25 °C, the nHAp/SDS and nanosilica concentrations increased the plastic viscosity by 20–90 % and 10–70 %, respectively. The inhibitory effect of nHAp/SDS surpasses that of conventional KCl-WBM and inorganic nanosilica. By adding 2.0 wt% nHAp/SDS to KCl-WBM, the shale swelling decreased from 10.1 to 4.7 % (a 53.4 % reduction). Nanosilica also reduced the swelling to 6.1 % (a 39.6 % reduction) during the LSM test at 25 °C. Under the DLSM test conditions, the shale swelling increased due to the activation of the clay platelet site at an increased temperature of 80 °C. For instance, between 25 and 80 °C, the DLSM test revealed that the shale plug height expanded from 6.1 to 9.8 % for 2.0 wt% nanosilica, 4.7–7.6 % for 2.0 wt% nHAp/SDS, and 10.1–18.8 % for KCl-WBM. Furthermore, the recovery rate of hot-rolled shale plugs with KCl-WBM increased from 89.8 to 96.2 % for nHAp/SDS and 76.6 to 88.8 % for nanosilica from the initial rates of 52.1–63.3 % between 65 and 120 °C. The contact angle results showed that nHAp/SDS is hydrophobic, reducing shale-water attraction. Moreover, the 12 nm nanosilica matches nanopore sizes to partially block shale pores. This research found that nHAp/SDS has the potential to improve wellbore stability.